Novel iridium complexes as yellow phosphorescent emitters for single-layer yellow and white polymer light-emitting diodes. Issue 27 (27th June 2016) - Liang, Aihui; Huang, Gui; Dong, Sheng; Zheng, Xiaoyan; Zhu, Jia; Wang, Zhiping; Wu, Wenjin; Zhang, Jie; Huang, Fei
Abstract : Both yellow and white polymer light-emitting devices are achieved using novel yellow phosphorescent iridium complexes with triphenylamine- and fluorene-functionalized cyclometalating ligands as dopants. Abstract : We have designed two novel yellow phosphorescent iridium complexes with triphenylamine- and fluorene-functionalized cyclometalating ligands that are capable of producing highly efficient yellow and white polymer light-emitting devices (PLEDs). Both yellow and white-light-emission devices are achieved with an identical single-emission-layer configuration of ITO/PEDOT:PSS/emission layer (EML)/CsF/Al. For the yellow phosphorescent PLEDs based on Y1, the best device performances with a peak luminous efficiency (LE) of 15.1 cd A −1 and a peak external quantum efficiency (EQE) of 7.6% are achieved. More importantly, the two-emitting-component WPLEDs containing iridum(iii )bis(2-(4, 6-difluorophenyl)-pyridinato-N, C 2′ ) picolinate (FIrpic) as blue and Y1 as yellow phosphors doped into a PVK:OXD-7 matrix at an appropriate ratio exhibited a maximum LE of 14.7 cd A −1, a maximum EQE of 8.6%, a maximum luminance of 5586 cd m −2 and Commission Internationale de L'Eclairage (CIE) coordinates of (0.33, 0.42) which are close to the standard for white light emission. Moreover, at a luminance for practical application of 1000 cd m −2, a good forward viewing LE of 14.4 cd A −1 is obtained with a very slight decrease.